Acquisition and Monitoring System for TEG Characterization - O. H. Ando; C. L. Izidoro; J. M. Gomes; J. H. Correia; J. P. Carmo; L. Schaeffer (International Journal of Distributed Sensor Networks)
This paper presents an acquisition system for measuring and characterization of thermoelectric generators (TEGs) for energy harvesting purposes on wireless sensors networks (WSNs). This system can monitor and characterize up to three TEGs simultaneously and is comprised of two main electronic circuits: the first one is composed of 12 input channels being three for reading voltage, three for reading current by making use of instrumentation amplifiers (ACS712), and six thermocouples for signal reading (<400°C). The second electronic circuit consists of a proportional-integral-derivative (PID) controller with two pulse width modulation (PWM) input channels for controlling the heat (thermoresistance) and cooling (controlled cooler) sources, respectively, following a predefined temperature gradient. The TEG measured data for the voltage, current, and temperature can be acquired in real-time with an application written on Delphi language and displayed both through a numeric and graphical display. In order to validate the precision and accuracy two commercial TEG modules (inbC1-127.08HTS) compatible with temperatures up to 200°C without signal degradation were used in series. The functional prototype of the implemented system had a cost under ≈430 USD, making it suitable where a good knowledge of the electrical characteristics of TEGs is of major interest, especially on cogeneration systems.